Contrasting Tensions Between Patients and PCPs in Chronic Pain Management: A Qualitative Study. Issue 11 (19th July 2013) - Bergman, Alicia A.; Matthias, Marianne S.; Coffing, Jessica M.; Krebs, Erin E.
Abstract Objective With greater scrutiny on primary care providers' (PCPs) approaches to chronic pain management, more research is needed to clarify how concerns and uncertainties about opioid therapy affect the ways both patients with chronic pain and PCPs experience primary care interactions. The goal of this qualitative study was to develop a better understanding of the respective experiences, perceptions, and challenges that patients with chronic pain and PCPs face communicating with each other about pain management. Design Purposive and snowball sampling techniques were used to identify 14 PCPs. Patients who received ≥6 opioid prescriptions during the prior year were selected at random from the panels of participating physicians. Face‐to‐face in‐depth interviews were conducted individually with patients and PCPs. Setting VISN 11 Roudebush VA Medical Center (RVAMC) in Indianapolis, Indiana. Subjects Fourteen PCPs and 26 patients with chronic pain participated. Methods An inductive thematic analysis was conducted separately with patient and PCP interview data, after which the emergent themes for both groups were compared and contrasted. Results Three notable tensions between patients and PCPs were discovered: 1) the role of discussing pain versus other primary care concerns, 2) acknowledgment of pain and the search for objective evidence, and 3) recognition of patient individuality and consideration of relationship history. Conclusions Competing demands of primary care practice, differing beliefs about pain, and uncertainties about the appropriate place of opioid therapy in chronic pain management likely contributed to the identified tensions. Several clinical communication strategies to help PCPs mitigate and manage pain‐related tensions are discussed.